Validity and Reliability of Turkish Version of the Identification Pain Questionnaire in the Assessment of Neuropathic Pain - Aslıhan UZUNKULAOĞLU; Duygu KERİM and Saime AY and Süreyya ERGİN (Archives of Rheumatology, 2019)
Objectives: This study aims to assess the validity and reliability of a Turkish version of the identification (ID) pain (ID pain-T) questionnaire in Turkish patients. Patients and methods: The Turkish version of ID pain questionnaire was obtained after translation from English into Turkish. The study included 194 patients of which 100 (34 males, 66 females; mean age 59.8±14.3 years; range, 28 to 88 years) were diagnosed as neuropathic pain (NP) and 94 (31 males, 63 females; mean age 47.2±16.5 years; range, 20 to 78 years) were diagnosed as non-neuropathic pain. Patients with mixed-type pain, cancer pain, headaches, substance abuse, severe depression or fibromyalgia syndrome were excluded. Results: The reliability and consistency of ID pain-T questionnaire were acceptable, with a Cronbach’s alpha coefficient of 0.701. Statistical analysis of the ID pain-T questionnaire calculated an optimal cut-off score of ≥2 for determining NP with a sensitivity of 77.2% and a specificity of 85%. Further, with an excellent value of 0.92 for area under the curve, a good diagnostic value was indicated. Conclusion: The Turkish version of ID pain questionnaire assessed in the present study is a valid and reliable self-administered questionnaire to identify NP in Turkish patients.